Giving birth in Switzerland: a qualitative study exploring migrant women’s experiences during pregnancy and childbirth in Geneva and Zurich using focus groups - J. Sami; K. C. Quack Lötscher; I. Eperon; L. Gonik; B. Martinez de Tejada; M. Epiney; N. C. Schmidt (Reproductive Health, 2019)
Abstract Background Migrant mothers in high-income countries often encounter more complications during pregnancy, delivery, and the postpartum period. To enlighten health care providers concerning potential barriers, the objective of this study was to explore positive and negative experiences with maternal health services in the University Hospitals of Geneva and Zurich and to describe barriers to maternity services from a qualitative perspective. Methods In this qualitative study, six focus groups (FGs) were conducted involving 33 women aged 21 to 40 years. All FG discussions were audio-recorded and later transcribed. Data were analysed using a thematic analysis approach assisted by the Atlas.ti qualitative data management software. Results Positive experiences included not only the availability of maternity services, especially during emergency situations and the postpartum period, but also the availability of specific maternity services for undocumented migrants in Geneva. Negative experiences were classified into either personal or structural barriers. On the personal level, the main barriers were a lack of social support and a lack of health literacy, whereas the main themes on the structural level were language barriers and a lack of information. Conclusion Structural adaptation is necessary to meet the needs of the extremely diverse population. The needs include (1) the provision of specific information for migrant women in multiple languages, (2) the availability of trained interpreters who are easily accessible to health care providers, (3) specifically trained nurses or social assistance providers to guide migrants through the health system, and (4) a cultural competence-training programme for health care providers.